Levels of cytokines in extended purulent peritonitis and methods of immunocorrection - E. T. Mammadova (Клінічна хірургія, 2020)
Objective. Comparative studying of the cytokines secretion dynamics in extended purulent peritonitis in postoperative period on background of the standard basic therapy and its combination with cytokinotherapy.